2.2–2.7 μm side wall corrugated index coupled distributed feedback GaSb based laser diodes. (June 2015) - Gaimard, Q; Larrue, A; Triki, M; Adelin, B; Nguyen-Ba, T; Rouillard, Y; Gauthier-Lafaye, O; Teissier, R; Vicet, A
Abstract We report on the modeling, growth, processing, characterization and integration in a gas detection setup of side wall corrugated distributed feed-back antimonide diode lasers emitting at 2.28 and 2.67 μm. The laser structures were grown by molecular beam epitaxy on GaSb substrate. Ridge lasers were fabricated from the grown wafers according to the following process: a second order Bragg grating was defined on the sides of the ridges by interferometric lithography, optical lithography and etched in a Cl-based inductively coupled plasma reactor. The devices exhibit a power reaching 40 mW, a side mode suppression ratio better than 28 dB and a tuning range of 3 nm at room temperature. One of these devices was successfully integrated in a tunable diode laser absorption spectroscopy setup, thus demonstrating that they are suitable for gas analysis.